A RELIABILITY-CENTRIC APPROACH TO ENERGY EFFICIENCY IN CLOUD COMPUTING SYSTEMS - Dileep Kumar Reddy Lankala, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article presents a reliability-centric framework for achieving energy efficiency in cloud computing systems while maintaining high levels of service reliability. The article integrates adaptive resource management strategies, workload-aware scaling, and predictive analytics to optimize energy consumption across data center operations. By combining advanced machine learning techniques, including deep reinforcement learning and neural networks, with sophisticated power management mechanisms, the system demonstrates significant improvements in resource utilization and energy efficiency. The implementation leverages web technology principles and smart applications to achieve optimal results across various operational scenarios. Through comprehensive experimental evaluation in both simulated and real-world environments, the article proves effective in reducing energy consumption while maintaining critical reliability metrics, making it particularly suitable for mission-critical industries requiring both environmental sustainability and operational excellence.